Adaptation of the Cognitive Demands of Flexible Work Scale (CODE) for the Indonesian Context: Validation and Psychometric Analysis - Nurkholis, Uswatun Hasanah; Wirawan, Hillman; Zulkifli, Az-Zahra Rizqi Quraini M.; Fahreza, Rizky Nur; Firdaus, Findra Anugrah Putri (PINISI Discretion Review, 2025)
This study aims to adapt and validate the Cognitive Demands of Flexible Work Scale (CODE) instrument into the Indonesian context. The original instrument, developed by Prem et al. (2021), measures four dimensions of cognitive demands in flexible work: Structuring of work tasks, Planning of working times, Planning of working places, and coordinating with others. The adaptation process involved forward-back translation, field testing, and psychometric analysis using a sample of 252 workers in South Sulawesi. The results of the Confirmatory Factor Analysis (CFA) showed a good model fit (CFI = 0.983, TLI = 0.976, RMSEA = 0.047), with all factor loadings significant (λ > 0.70). Reliability, as measured by omega coefficient (ω = 0.795–0.881) and Cronbach’s alpha (α = 0.788–0.875), met the criteria for acceptance. These findings support the validity and reliability of the Indonesian version of the CODE instrument, although there were minor variations in the correlation patterns among dimensions compared to the original version. This adaptation provides a valid tool for measuring the cognitive demands of flexible workers in Indonesia, with practical implications for human resource policy development and further research. In addition, this instrument can also be used to identify groups of workers who are most vulnerable to cognitive demands, such as those in leadership positions, those with higher educational backgrounds, or those working under flextime and flexplace systems. The results can serve as a basis for organizations to design more targeted interventions.